PERSEPSI DAN MINAT ESPORT PUBG MOBILE DALAM MENINGKATKAN KESEJAHTERAAN KELUARGA PADA REMAJA DESA JEMBAYAN - septiyani, sely; Noorhya Akhmar Ramadhan Putri, Eva; Zainuddin (I-Con Media, 2025)
Esports, including its popularity in the PUBG Mobile game, has become a global phenomenon that not only affects individual players, but also their families and surrounding communities. . In Jembayan Village, where teenagers are the dominant group in exploring technology and digital entertainment, perception and interest in PUBG Mobile esports plays an important role in the dynamics of family welfare. This research aims to understand how parents' perceptions and teenagers' interest in PUBG Mobile esports affect the welfare of families in the village.  This study uses a qualitative approach with in-depth interview techniques with parents and teenagers in Jembayan Village. The results show that parents' perceptions of esports tend to vary from skeptical to accepting, depending on their understanding of the benefits and risks involved. On the other hand, teenagers' interest in esports, especially PUBG Mobile, often centers on the competitive and social aspects of the game, which they perceive as an interesting form of entertainment and an opportunity to improve their skills in coordination, strategy and teamwork. In conclusion, perception and interest in PUBG Mobile esports not only affects individual teenagers, but also family dynamics in Jembayan Village. With the right approach, esports can be a tool to improve family well-being by promoting positive engagement, open communication and the development of skills relevant to this digital age.